Numerical simulation of impact cratering on granular material - Wada, Koji; Senshu, Hiroki; Matsui, Takafumi (Icarus (New York, N.Y. 1962), 2006)
A new numerical code based on the Distinct Element Method (DEM) is developed to study the impact cratering processes on granular material. This code has a potential advantage to simulate the cratering process on granular material, since the movement of discrete particles can be treated. To show the physical plausibility of this code, we conduct 3-D numerical simulations of vertical impact into granular material targets that consist of 384,000 particles, and compare the results with those from experimental studies. It is shown that the excavation stage of cratering derived from experimental studies is represented well by our simulation: the size of the crater cavity, and the ejecta velocity and angle distributions are consistent with those obtained in laboratory experiments. The impact simulation code developed in this study is thus suggested to be useful for the analysis of the impact cratering process on granular material.